Heterozygous variants in ZBTB7A cause a neurodevelopmental disorder associated with symptomatic overgrowth of pharyngeal lymphoid tissue, macrocephaly, and elevated fetal hemoglobin. Issue 1 (13th September 2021) - von der Lippe, Charlotte; Tveten, Kristian; Prescott, Trine E.; Holla, Øystein L.; Busk, Øyvind L.; Burke, Katherine B.; Sansbury, Francis H.; Baptista, Júlia; Fry, Andrew E.; Lim, Derek; Jolles, Stephen; Evans, Jennifer; et al.
Abstract: By clinical whole exome sequencing, we identified 12 individuals with ages 3 to 37 years, including three individuals from the same family, with a consistent phenotype of intellectual disability (ID), macrocephaly, and overgrowth of adenoid tissue. All 12 individuals harbored a rare heterozygous variant in ZBTB7A which encodes the transcription factor Zinc finger and BTB‐domain containing protein 7A, known to play a role in lympho‐ and hematopoiesis. ID was generally mild. Fetal hemoglobin (HbF) fraction was elevated 2.2%–11.2% (reference value <2% in individuals > 6 months) in four of the five individuals for whom results were available. Ten of twelve individuals had undergone surgery at least once for lymphoid hypertrophy limited to the pharynx. In the most severely affected individual (individual 1), airway obstruction resulted in 17 surgical procedures before the age of 13 years. Sleep apnea was present in 8 of 10 individuals. In the nine unrelated individuals, ZBTB7A variants were novel and de novo. The six frameshift/nonsense and four missense variants were spread throughout the gene. This is the first report of a cohort of individuals with this novel syndromic neurodevelopmental disorder.